Structure and morphology absorber material base on Iron Sand with SiO_2 fortification from water hyacinth - Hidayat, Sony; Fianti, Fianti; Nurbaiti, Upik; Astuti, Budi (Journal of Natural Sciences and Mathematics Research, 2024)
Electromagnetic radar technology has become integral in various innovations, such as military, air navigation, and weather monitoring. However, the ability of radar to detect objects accurately creates vulnerability to detection by other parties, raising security and confidentiality issues. Therefore, the development of electromagnetic absorber material technology is becoming increasingly important, especially in the military. One promising effort is using smart magnetic pigments as electromagnetic wave absorber materials. This material can be synthesized from metal waste and iron sand, which have high permeability and permittivity. However, synthesizing effective and economical smart magnetic materials is still challenging. Iron sand is one of the potentially abundant material solutions. This study aims to synthesize and characterize smart magnetic pigments ( ) from iron sand and silica ( ) from water hyacinth ash as electromagnetic wave absorber materials. The methods used include the extraction of silica from water hyacinth by a slow heating method at high temperatures and the synthesis of magnetite from iron sand by the coprecipitation method. The resulting material was then composited into an Unsaturated Polyester Resin (UPR) matrix and tested for electromagnetic wave absorption. The developed composite material has a porous structure (3.63 µm, porosity 15.746%) with synergistic properties between dielectric and   ferromagnetic. The Si-O-Si and Fe-O functional groups (FTIR) and the crystal phases , Cristobalite, and Butlerite (XRD) strengthen the material interactions. This combination of characteristics proves that the composite material can absorb and dampen electromagnetic waves.